2021
DOI: 10.1163/23644583-bja10013
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Choir Ecology and the Zoom-machinic

Abstract: covid-19 has changed the way we sing in choirs and has seen the extraordinary uptake of Zoom as a video chat platform across society. This is a reflective tale of four choirs members and their insights into how they improvised with traditional choir singing in a Zoom space. It consideres how zoom pedagogies allowed them to bridge social isolation during the pandemic. It includes the voices of the conductor; music teacher/technician; the voice of a media savvy artist choir member and finally the voice of a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
1
Order By: Relevance
“…Nevertheless, it is noteworthy that Zoom has been widely used as a concert platform during the COVID-19 pandemic. This is the case for children and parents (Sandra and Kusuma, 2020), patients, caregivers, and hospital staff (Ambler et al, 2020), as well as for choirs and other groups of joint music makers who have used Zoom as a virtual rehearsal space (Grushka et al, 2021;Onderdijk et al, 2021). This previous research suggests that connectedness is a central theme when examining Zoom's efficacy (Ambler et al, 2020;Grushka et al, 2021).…”
Section: Impact Of Agency Presence and Social Context On Social Connectednessmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is noteworthy that Zoom has been widely used as a concert platform during the COVID-19 pandemic. This is the case for children and parents (Sandra and Kusuma, 2020), patients, caregivers, and hospital staff (Ambler et al, 2020), as well as for choirs and other groups of joint music makers who have used Zoom as a virtual rehearsal space (Grushka et al, 2021;Onderdijk et al, 2021). This previous research suggests that connectedness is a central theme when examining Zoom's efficacy (Ambler et al, 2020;Grushka et al, 2021).…”
Section: Impact Of Agency Presence and Social Context On Social Connectednessmentioning
confidence: 99%
“…This is the case for children and parents (Sandra and Kusuma, 2020), patients, caregivers, and hospital staff (Ambler et al, 2020), as well as for choirs and other groups of joint music makers who have used Zoom as a virtual rehearsal space (Grushka et al, 2021;Onderdijk et al, 2021). This previous research suggests that connectedness is a central theme when examining Zoom's efficacy (Ambler et al, 2020;Grushka et al, 2021). In the present study performers and participants did not take full advantage of Zoom's features (e.g., only two participants used Zoom's chat function), and it is likely such communicative features can be further exploited to facilitate connectedness among/between audiences and performers.…”
Section: Impact Of Agency Presence and Social Context On Social Connectednessmentioning
confidence: 99%
“…Interview data indicated that choirs who shifted from traditional, live performances to virtual, multi-track recorded formats during the pandemic found it difficult initially, citing barriers to participation from technological skills, costs, availability and reliability, as well as the difficulty of singing together without being able to hear one another, or problems finding quiet space to record, which ultimately negatively affected their enjoyment (Daffern et al, 2021: 6). Similarly, the experience of lockdown itself and the ‘period of personal uncertainty and anxiety about how they could sustain choir membership’ (Grushka et al, 2021: 5) contributed to difficulties in establishing a virtual choir.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging research on virtual choirs has tended to focus either on the technical or technological aspects of creating a virtual choir, aimed predominantly at musicians, sound engineers and educators (See, for example, Eren and Öztug, 2020; French, 2017; Senecal and Gazda, 2010), interview data based on the affordances and constraints of that participation (See, for example, Daffern et al, 2021; Grushka et al, 2021; Hirst, 2021), or are written by conductors reflecting on their experiences of running a virtual choir (See, for example, Galván and Clauhs, 2020; Grushka et al, 2021). Carvalho and Goodyear’s (2014) discussion on the architecture of learning space in Eric Whitacre’s Virtual Choir is unique in that in addition to participant interviews, it also describes detail of the physical and technological aspects of the virtual choir in a pre-pandemic world and, in particular, the link between real and virtual spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Choirs throughout the world have survived the onslaught of Covid-19 through the use of various technological platforms. As described by Grushka et al (2021), the usual social ecology of a choir providing friendship, support and the experience of singing together, has moved into a virtual realm.…”
Section: A Pause Becomes An Endmentioning
confidence: 99%